Open Mesh Hernioplasty versus Laparoscopic Total Extraperitoneal Mesh Repair in the Treatment of Inguinal Hernia - Syeda Saima Qamar Naqvi, Sidra Abbas, Hammad Hanif, Rizwan Ahmed Khan, Syed Mohammad Abdullah Bukhari, Syed Adnan Ahmed (Pakistan Journal of Medical & Health Sciences, 2023)
Background: There are multiple techniques used worldwide to repair inguinal hernia. The open mesh hernioplasty is easy to carry out, tension free repair and having good long term results but has few complications as well. Recently the laparoscopic repair of inguinal hernia is the best option because of its merits like lower recurrence rate, lesser postoperative pain, fast recovery and lower risk of complications. The results are controversial so there is a need to evaluate that which technique is better in our population so the aim of current study was to compare the outcome of open mesh hernioplasty versus laparoscopic total extra-peritoneal mesh repair in the treatment of inguinal hernia. Methods: A randomized controlled trial was conducted in the department of surgery, Ziauddin hospital, Karachi during May to December 2021. Patients included in the study were divided into two groups, Group A included those who underwent open mesh hernioplasty while Group B contained patients treated with laparoscopic total extra peritoneal mesh repair. The complication including scrotal hematoma was assessed clinically and confirmed by ultrasound then putted on follow up for two weeks. Data was collected on self-designed proforma. Statistical Package for Social Science (SPSS) version 20 was used for analysis of data. Results: The mean age of the study participants was 36.2±5.6 years. In both group A and B, majority of patients were having right sided inguinal hernia. In Group A, majority of patients were presented with direct inguinal hernia while majority of Group B patients were presented with indirect inguinal hernia but the p-value was non-significant. Postoperative scrotal hematoma was found in 19.5% of the study participants among them 7.8% participant were having direct inguinal hernia and 11.7% presented with indirect inguinal hernia. The frequency of scrotal hernia in patients of Group A, having open mesh hernioplasty was 15.6% while in Group B lesser frequency of postoperative scrotal hematoma was noted and the results were highly significant. Conclusion: It can be concluded that laparoscopic total extra-peritoneal mesh repair is the best technique for repairing inguinal hernia because of its minimal postoperative complications in comparison to open mesh hernioplasty. It is recommended to consider laparoscopic total extra-peritoneal mesh repair as the first line treatment option in the case of inguinal hernia. Keywords: Inguinal Hernia, Laparoscopic total extra-peritoneal mesh repair, Open mesh hernioplasty